Notes from a small island - Bryson, Bill. (New York : Avon Books, 1995)
Before returning to America after spending twenty years in Britain, the author decided to tour his second home and presents a look at England's quirks and its endearing qualities
Keywords: Bryson, Bill -- Travel -- England; England -- Civilization -- 20th century; England -- Description and travel